Emergency remote learning and TDIC's during the COVID-19 pandemic: Impulses and obstacles - Miranda, Gilmar dos Santos Sousa (Seven Editora, 2023)
This article aims to report the experience of the researcher in a working group constituted to assist in the uninterrupted maintenance of the academic activities of a public educational institution during the COVID-19 pandemic. The group was constituted in a collaborative institutional effort of technicians and teachers. The researcher works in the technical staff of the institution, as a professional of Information and Communication Technology (ICT), however, also acts as a professor and researcher in the field of technologies in education. This work is intended to history the practices and activities of the group, designed and built collaboratively, focusing on the students and teachers of the institution, seeking to contribute to the existing projects of remote activities. This work portrays the effort to build and apply a set of actions that sought to reproduce, in a virtual teaching environment, the production and dissemination of content and teaching activities to integrate and link to teaching and learning actions in all units of the institution. Through free technological tools, solutions were proposed to incorporate and enrich teaching practices, as well as to promote the creation of educational policies and teacher training. The methodological basis used was that of participant research, which according to Brandão (1990) allows an active and critical positioning as being a possible intervention and search for transformation through the construction of new concepts and values from the collective dialogical-dialectical participation. It is expected that this report will have a significant impact not only on emergency remote teaching but as studies for water education grow. In the State of Minas Gerais, the "Conexão Se Liga" project has so far trained approximately 15,000 teachers, but the project is still ongoing and can serve 60,000 teachers from the state network of Minas Gerais. DOI:https://doi.org/10.56238/emerrelcovid19-001